Politics of development in postcolonial India: English-medium education and social fracturing - Faust, David; Nagar, Richa (2001)
While education in English has been advocated as a unifying and modernising force, it is also seen as a marker of imperialism and class privilege and a terrain of struggle among elite groups. Ruptures in such a class-divided educational system in turn shape specific debates over development, democracy and social change. Uneven empowerment that an education in English generates also has its fallout in an increasing polarisation, fracturing and violence against caste, gender and religious lines. - Reproduced
Keywords: Education - India; Education